Valuation Analysis of Joint Venture Value through Acquisition Process: Case Study of PT Pelat Timah Nusantara by PT Bumi Resources Mineral - Wulandari, Rayuli; Syawaldi, Ahmad; Heikal , Jerry (Jurnal Sains dan Teknologi, 2024)
The study aims to calculate the bid price of the combined company through the acquisition between PT Bumi Resources Mineral Tbk and PT Pelat Timah Nusantara Tbk using M&A valuation and structuring models. The valuation model includes discounted cash flow (DCF) analysis, comparable company analysis, and market value methods. M&A structuring involves financial arrangements, legal considerations, and integration strategies to merge the operations of both companies. The acquisition was made at a bid price of IDR 115.56 per share. The equity value of the target company was 2.87 T with a per-share value of 1140.79, while the equity value of the acquiring company was 4.21 T with a per-share value of 29.76. After the acquisition, the new company's equity value is 22.8 T with a per-share value of 115.56. Findings indicate that the bid of the new company may be considered undervalued because the per-share equity value is lower compared to pre-acquisition, suggesting unrealized potential value if the bid price per share is below the pre-acquisition equity value per share.